1984
DOI: 10.1042/bj2220363
|View full text |Cite
|
Sign up to set email alerts
|

Fructose is a good substrate for rat liver ‘glucokinase’ (hexokinase D)

Abstract: Rat liver 'glucokinase' (hexokinase D) catalyses the phosphorylation of fructose with a maximal velocity about 2.5-fold higher than that for the phosphorylation of glucose. The saturation function is hyperbolic and the half-saturation concentration is about 300 mM. Fructose is a competitive inhibitor of the phosphorylation of glucose with a Ki of 107 mM. Fructose protects hexokinase D against inactivation by 5,5'-dithiobis-(2-nitrobenzoic acid), and the apparent dissociation constants are about 300 mM in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

1984
1984
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 36 publications
2
43
0
Order By: Relevance
“…The Hill coefficient (h) was about 1.5, i. e. the same value as obtained with glucose [5,61. In contrast, the saturation functions of hexokinase D with 2-deoxyglucose [17, 241 and with fructose [4] were hyperbolic ( h = 1.0). In this report the Hill coefficient and the Hill plot have been used only to measure the degree of cooperativity with no implication of mechanism.…”
Section: Saturation Function Of Hexokinase D With Mannosementioning
confidence: 98%
See 1 more Smart Citation
“…The Hill coefficient (h) was about 1.5, i. e. the same value as obtained with glucose [5,61. In contrast, the saturation functions of hexokinase D with 2-deoxyglucose [17, 241 and with fructose [4] were hyperbolic ( h = 1.0). In this report the Hill coefficient and the Hill plot have been used only to measure the degree of cooperativity with no implication of mechanism.…”
Section: Saturation Function Of Hexokinase D With Mannosementioning
confidence: 98%
“…The relative efficiency of mannose, 2-deoxyglucose and N-acetylglucosamine in their effects on the cooperative behaviour of glucose phosphorylation appears in Table 2, where [4] are also included. It is interesting to note that fructose, a relatively poor inhibitor, appears as the most efficient, as the relative concentration necessary to bring the Hill coefficient to 1.0 was about three times lower than the relative concentration required by mannose and ten times lower than that required by 2-deoxyglucose.…”
Section: Specgicitymentioning
confidence: 99%
“…In method A the phosphorylation was coupled to glucose-6-phosphate dehydrogenase and the rate of reduction of NADP was measured at 340 nm in a Gilford spectrophotometer 2400 provided with a thermospacer maintained at 30°C. The assay medium was that of Cardenas et al (18). The same reaction mixture with ATP omitted acted as a blank.…”
mentioning
confidence: 99%
“…As mentioned already, hexokinase D from mammalian liver is an example of an enzyme that is cooperative with respect to glucose, and noncooperative with respect to fructose, 27 though some authors 34 have reported cooperativity. The specificity of this isoenzyme has been a point of contention since it was discovered, 28,35 and the suggestion of the name "glucokinase" 36 was intended to be provisional until "further characterization of the enzyme could make more appropriate some other name".…”
Section: Application To Mammalian Hexokinasesmentioning
confidence: 98%
“…However, it was not initially realized that hexokinase D (also called hexokinase IV), the isoenzyme characteristic of mammalian liver, is cooperative with respect to glucose, and thus has no K m for glucose, though it follows Michaelis-Menten kinetics with respect to fructose. 27 This complication, together with its high half-saturation concentrations for both substrates, led to much confusion about its specificity, a confusion that persists in the misleading name glucokinase that remains common for this isoenzyme. The lack of an established measure of specificity for a cooperative enzyme led one of us 28 to compare substrates in terms of k cat /K 0.5 .…”
Section: Introductionmentioning
confidence: 99%